Improving a Skills of EFL Students Using Duolingo in a Rural Madurese School - Aini, Syarifah; Raihany, Afifah; Rahmawati, Fithriyah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Speaking skill is one of the main challenges for EFL (English as a Foreign Language) learners, especially in rural areas with limited access to authentic communication and digital technology. This study aimed to examine the effectiveness of the Duolingo application in improving the English-speaking skills of eighth-grade students at MTs Nurul Huda Al Maroniyah Sampang. This research employed a pre-experimental one-group pretest-posttest design with a total of 30 students as participants. The research procedure consisted of a pretest, three weeks of treatment using Duolingo, and a posttest. The main research instrument was a speaking test that assessed five aspects: fluency, grammar and accuracy, pronunciation, vocabulary use, and comprehensibility, scored on a 1–5 Likert scale. Data from the pretest and posttest were analyzed using the Wilcoxon Signed-Rank Test via SPSS 25 to determine the statistical significance, and effect size was calculated to measure the magnitude of improvement. The results revealed a statistically significant improvement in students’ speaking skills (p = 0.000) with a very large effect size (r = 0.861). These findings indicate that Duolingo can be an effective, engaging, and practical tool for developing speaking skills in resource-limited educational contexts, particularly in rural Islamic junior high schools in Indonesia. Future studies are recommended to explore the combination of Duolingo with live speaking practice or compare its effectiveness with other mobile-assisted language learning applications.Keterampilan berbicara merupakan salah satu tantangan utama bagi siswa EFL (English as a Foreign Language), terutama di daerah pedesaan yang memiliki akses terbatas terhadap komunikasi autentik dan teknologi digital. Penelitian ini bertujuan untuk mengetahui efektivitas aplikasi Duolingo dalam meningkatkan kemampuan berbicara bahasa Inggris siswa kelas VIII MTs Nurul Huda Al Maroniyah Sampang. Penelitian ini menggunakan desain pra-eksperimental one-group pretest-posttest dengan total 30 siswa sebagai peserta. Prosedur penelitian meliputi tahap pra-ujian, perlakuan menggunakan aplikasi Duolingo selama tiga minggu, dan pasca-ujian. Instrumen penelitian berupa tes berbicara yang menilai lima aspek, yaitu kefasihan, tata bahasa dan ketepatan, pelafalan, penggunaan kosakata, dan keterpahaman, dengan skala penilaian Likert 1–5. Data pretest dan posttest dianalisis menggunakan uji Wilcoxon Signed-Rank melalui SPSS 25 untuk melihat signifikansi perbedaan, serta dihitung ukuran efek (effect size) untuk mengetahui besar pengaruh perlakuan. Hasil penelitian menunjukkan peningkatan kemampuan berbicara yang signifikan secara statistik (p = 0,000) dengan ukuran efek yang sangat besar (r = 0,861). Temuan ini menunjukkan bahwa Duolingo dapat menjadi alat yang efektif, menarik, dan praktis untuk mengembangkan keterampilan berbicara di lingkungan pendidikan yang minim sumber daya, khususnya di madrasah tsanawiyah pedesaan di Indonesia. Disarankan agar penelitian selanjutnya mengeksplorasi kombinasi Duolingo dengan praktik berbicara langsung atau membandingkan efektivitasnya dengan aplikasi pembelajaran bahasa lainnya.